Measuring Business Social Innovation and the Effectiveness of Corporate Social Responsibility Programs in Local Communities - Misrofingah Misrofingah; M. Anton Fatoni; Budi Akhmad Tarigan; Arif Riyanto (Jurnal Ilmu Sosial dan Humaniora, 2025)
There is minimal evaluation of Corporate Social Responsibility programs in improving the welfare and sustainability of micro, small, and medium enterprises (MSMEs) in the Jakarta area. The urgency of researching corporate social responsibility in supporting the growth and empowerment of local communities and the sustainability of MSMEs. The purpose of this study is to analyze the influence of Social Responsibility programs on the welfare of MSMEs through social innovation. The research approach uses a quantitative survey method. The sample consisted of 272 MSME actors in the city of Jakarta who were selected purposively. Data collection using questionnaires distributed online and in person by measuring cultural variables, community participation, social innovation, and MSME welfare. Data were analyzed using descriptive statistics assisted by SPSS Version 29.0 with regression analysis and hypothesis testing. The results show that Corporate Social Responsibility has a significant effect on the welfare of MSMEs (β = 0.310; p = 0.006) and economic innovation (R² = 0.894). Community participation is also significant (β = 0.321; p = 0.009). The model explains 91% of the variation in MSME welfare (R² = 0.910), with strong contributions from culture and social engagement. In conclusion, local social and cultural innovations can sustainably improve MSME welfare. Practical implications: Business actors and policymakers should integrate social innovation-based programs and actively engage the community to support inclusive local economic growth in Jakarta.